Credit Risk Capital and Interest Rates Shape Bank Net Interest Margin - Efriandy, Iwan; Rohman, Abdul; Budiman, Anton Indra (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Banking profitability is a critical indicator of financial system resilience and intermediation efficiency in emerging economies. Specific Background: Net Interest Margin (NIM) reflects banks’ ability to manage credit risk, capital adequacy, and macroeconomic fluctuations, particularly during periods of economic uncertainty in Indonesia’s banking sector from 2015–2024. Knowledge Gap: Previous studies have generally examined internal banking factors or macroeconomic variables separately, while limited evidence integrates credit risk, capital adequacy, interest rates, and inflation simultaneously in explaining NIM dynamics among Indonesian commercial banks. Aims: This study analyzes the relationships between Non-Performing Loans (NPL), Capital Adequacy Ratio (CAR), interest rates, inflation, and NIM using balanced panel data from 12 Indonesian commercial banks during 2015–2024. Results: Panel data regression using the Random Effect Model shows that NPL has a negative and significant relationship with NIM, indicating that rising credit risk reduces bank profitability through higher provisioning costs and lower net interest income. CAR demonstrates a positive but statistically insignificant relationship with NIM, suggesting that capital mainly functions as a stability buffer rather than a direct profitability driver. Interest rates also show an insignificant relationship with NIM, indicating indirect monetary policy transmission to banking margins. Novelty: This study integrates microprudential banking indicators and macroeconomic variables within a unified panel regression framework to explain NIM behavior in Indonesian commercial banks. Implications: The findings highlight the strategic importance of credit risk management and financial system stability for sustaining banking profitability and supporting effective banking intermediation. Highlights: Rising non-performing loans reduced banking profitability through higher provisioning pressure. Capital resilience primarily functioned as a financial stability buffer across commercial banks. Monetary policy transmission to banking margins occurred indirectly during the observation period. Keywords: Net Interest Margin, Credit Risk, Capital Adequacy Ratio, Interest Rates, Indonesian Commercial Banks